Subcutaneous Pectoral Edema After Arthroscopic Labral Repair Despite Normal Irrigation Fluid Usage and Surgery Duration - İnci Hazal Ayas; Yağız Oğul Akcan; Miray Haspolat; Mehmet Ali Tokgöz; İlke Keser; Ulunay Kanatlı (Orthopaedic Surgery)
ABSTRACT Objectives Edema after shoulder arthroscopic surgery poses concerns due to its potential complications such as compartment syndrome, nerve damage, and respiratory issues. This study aimed to investigate the acute accumulation of subcutaneous fluid after shoulder arthroscopy. Methods A prospective cohort study, providing Level III evidence was conducted on 50 patients undergoing arthroscopic shoulder surgery under interscalene block anaesthesia from September to December 2023. The patients were divided into two groups: rotator cuff repair (RCR, n = 29) and labral repair for shoulder instability (LR, n = 21). Subcutaneous fluid levels were measured preoperatively, postoperatively, and at discharge (24 h postsurgery) using the MoistureMeterD Compact at the neck, pectoral region, deltoid area, cubital fossa, and carpal tunnel. Data on surgery duration and irrigation fluid volume were documented. In the statistical analysis, repeated measures ANOVA and the independent‐samples t‐test were applied to compare parametric data, while the Friedman test and Mann–Whitney U test were used for nonparametric data. Results The average operation time was 29.0 ± 12.1 min for RCR and 30.0 ± 10.9 min for LR, with average irrigation fluid use of 3.8 ± 0.9 and 4.0 ± 0.7 L, respectively (both p > 0.05). There was no increase in subcutaneous edema in the neck and deltoid region in both groups. At discharge, the percentage of subcutaneous fluid increased in the cubital fossa (p = 0.04 for RCR; p < 0.001 for LR) and carpal tunnel (both p < 0.001) in oth groups, whereas pectoral edema increased only in the labral repair group (p = 0.04). Conclusions Subcutaneous pectoral edema can occur following arthroscopic labral repair, and increased fluid levels in the cubital fossa and carpal tunnel were observed in both rotator cuff and labral repairs, even in the absence of prolonged surgery or excessive irrigation fluid use. These findings highlight the need for careful postoperative management of edema after shoulder arthroscopy, particularly for labral repairs, with special attention to the pectoral region, cubital fossa, and carpal tunnel to prevent potential complications. The registry is sponsored by the United States National Library of Medicine (www.clinicaltrials.gov); Registry Name: Examination of Edema After Arthroscopic Shoulder Surgery ID: NCT06014203.